Hepatitis G virus infection among Iraqi patients with Chronic liver diseases. - Al-Obeidy, Eman Sh.; Abdullah, Shatha F.; Mukhlis, Faiza A. (Journal of the Faculty of Medicine Baghdad, 2010)
Background: The hepatitis G virus( HGV), also called hepatitis GB virus, as a member of the Flaviviridae family distantly related to hepatitis C virus (HCV), Little is known about the frequency of HGV infection, the nature of the illness, or how to prevent it. What is known is that transfused blood containing HGV has caused some cases of hepatitis. They infect humans, but are not known to cause human disease. This virus can be transmitted efficiently by blood transfusion and by other parenteral mechanisms. Transient and long lasting infections with HGV have been documented in man. Patients and methods: HBs Ag, Anti-HCV IgG and Anti-HGV IgG were detected by Enzyme-Linked Immunosorbent Assay (ELISA).HCV RNA on the other hand, has been detected using PCR technique in the serum of 75 Iraqi patients with chronic liver diseases in comparison to 15 healthy individuals. Results: HGV infection was detected in 25% of blood donors, 30% of chronic hepatitis C, 25% of chronic hepatitis B, and 20% of cryptogenic chronic liver disease. HGV infected patients tended to be younger than non-infected patients but no differences concerning sex, possible source of infection, clinical manifestations, biochemical and virological parameters, or severity of liver lesions were found. Conclusions: The percentage of HGV infection in chronic liver disease seems to be relatively high in our area 19 out of 90cases (21.11%). Infection with HGV does not seem to play a significant pathogenic role in patients with chronic liver disease related to chronic HBV or HCV infection, or in those with cryptogenic chronic liver disease.